2019
DOI: 10.1002/stem.2992
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Sympk and Oct4 Promotes Mouse Embryonic Stem Cell Proliferation

Abstract: The scaffold protein Symplekin (Sympk) is involved in cytoplasmic RNA polyadenylation, transcriptional modulation, and the regulation of epithelial differentiation and proliferation via tight junctions. It is highly expressed in embryonic stem cells (ESCs), in which its role remains unknown. In this study, we found Sympk overexpression in mouse ESCs significantly increased colony formation, and Sympk deletion via CRISPR/Cas9 decreased colony formation. Sympk promoted ESC growth and its overexpression sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…We also cannot rule out that an increase in levels of some subunits of the complex may be associated with other roles in the cell besides mRNA 3’ end processing. For example, the symplekin subunit of CPSF also functions at the surface of the cell in tight junctions ( 89 ) and its interaction with Oct4 promotes the activity of this transcriptional driver of cell stemness ( 90 ). Thus, subcomplexes can exist within the cell, suggesting the intriguing possibility that this could be another point at which polyadenylation capacity of the cell could be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…We also cannot rule out that an increase in levels of some subunits of the complex may be associated with other roles in the cell besides mRNA 3’ end processing. For example, the symplekin subunit of CPSF also functions at the surface of the cell in tight junctions ( 89 ) and its interaction with Oct4 promotes the activity of this transcriptional driver of cell stemness ( 90 ). Thus, subcomplexes can exist within the cell, suggesting the intriguing possibility that this could be another point at which polyadenylation capacity of the cell could be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, SYMPK has been identified as a cofactor of RBFOX2 and NOVA2 to regulate alternative mRNA splicing ( Misra et al, 2015 ). Recently, it has been reported that SYMPK promotes the self-renewal and pluripotency of embryonic stem cells (ESCs) through interaction with OCT4 ( Yu et al, 2019 ). Nevertheless, the function of SYMPK in male germ cells is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Midbodies form during final stages of cytokinesis and are rich in microtubules that are stabilized by KIF20B (Janisch et al, 2018). In ESCs KIF20B expression levels are tightly regulated by Symplekin, which together with Oct4 control stem cell pluripotency expression profiles (Yu et al, 2019). Kif20b knockdown disrupts cellular polarization and cells display cytokinetic defects leading to the accumulation of apoptotic multinucleated cells (Georges et al, 2019).…”
Section: Kif20bmentioning
confidence: 99%